Dissemination of disaster communication technology through aslidslide early detection tools in Sonyo Hamlet, Jatimulyo Village, Kulon progo District - Adhianty Nurjanah; Iswanto Suwarno; Muhammad Ahmad Baballe; Nia Maharani Raharja; Dhiya Uddin Rijalusalam; Reza Alayi; Rachmad Andri Atmoko; Irfan Ahmad (Peneliti Teknologi Teknik Indonesia, 2021)
When a natural disaster occurs, effective disaster communication involving communication and information technology is an important thing that must be done to the community in the disaster-affected area. When the landslide disaster occurred in Soyono Jatimulyo Hamlet, Kulon Progo, in 2016 the community the role of community leaders such as the Hamlet Head was very vital, especially in terms of disaster communication to the hamlet community. However, based on the observation that the head of the hamlet as a disaster communicator, he still has limitations when carrying out the function of a disaster communicator, especially in terms of the use of communication and information technology and still needs to improve disaster mitigation capabilities. Priority problems are 1. Limited disaster communication technology, 2. Lack of disaster mitigation capabilities. Community empowerment methods as solutions to the proposed problems are: 1. Making disaster communication tools in the form of landslide early detection tools that can assist in disaster communication, 2. Community-based disaster mitigation training. The result of this service is the empowerment of the people of Dusun Sonyo Jatimulyo Kulon Progo in carrying out their vital duties as disaster communicators through landslide detection tools and an 80% increase in disaster mitigation capabilities of the Dusun Soyo Jatimulyo Kulon Progo community.